Differential Regulation of Self-reactive CD4+ T Cells in Cervical Lymph Nodes and Central Nervous System during Viral Encephalomyelitis - Savarin, Carine; Bergmann, Cornelia C.; Hinton, David R.; Stohlman, Stephen A. (Frontiers in Immunology, 2016)
Viral infections have long been implicated as triggers of autoimmune diseases, including Multiple Sclerosis (MS), a central nervous system (CNS) inflammatory demyelinating disorder. Epitope spreading, molecular mimicry, cryptic antigen and bystander activation have been implicated as mechanisms responsible for activating self-reactive (SR) immune cells, ultimately leading to organ-specific autoimmune disease. Taking advantage of coronavirus JHM strain of mouse hepatitis virus (JHMV) induced demyelination, this study demonstrates that the host also mounts counteractive measures to specifically limit expansion of endogenous SR T cells. In this model, immune mediated demyelination is associated with induction of SR T cells after viral control. However, their decline during persisting infection, despite ongoing demyelination, suggests an active control mechanism. Antigen-specific IL-10 secreting CD4+ T cells (Tr1) and Foxp3+ regulatory T cells (Tregs), both known to control autoimmunity and induced following JHMV infection, were assessed for their relative in vivo suppressive function of SR T cells. Ablation of Foxp3+ Tregs in chronically infected DEREG mice significantly increased SR CD4+ T cells within cervical lymph nodes (CLN), albeit without affecting their numbers or activation within the CNS compared to controls. In contrast, infected IL-27 receptor deficient (IL-27R-/-) mice, characterized by a drastic reduction of Tr1 cells, revealed that SR CD4+ T cells in CLN remained unchanged, but were specifically increased within the CNS. These results suggest that distinct regulatory T cell subsets limit SR T cells in the draining lymph nodes and CNS to maximize suppression of SR T cell mediated autoimmune pathology. The JHMV model is thus valuable to decipher tissue specific mechanisms preventing autoimmunity.